Draft Law on civil protection and the state of natural disaster – constitutional analysis - Lisiecka, Monika (Scientific Journal of Bielsko-Biala School of Finance and Law, 2022)
This article aims to analyse the reforms provided for in the draft Law on civil protection and the state of natural disaster and to assess them in terms of the paradigm of extraordinary measures. The research methodology is based on analysis of the provisions of the Constitution and ordinary statutes and a review of literature, including the historical-descriptive method analysis concerning the documentation of the legislative process. The research leads to a negative assessment of the Draft. The drafters’ failures concerning the definiteness of the proposed regulations, blurring the dichotomous division into an extraordinary measure and normal functioning of the State, and excessive interference in the independence of local self-government are revealed.